2008
DOI: 10.1002/lt.21384
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and focused hepatitis B virus nucleocapsid–specific T-cell immunity in liver transplant recipients compared to individuals with chronic and self-limited hepatitis B virus infection

Abstract: Hepatitis B virus (HBV) recurrence after orthotopic liver transplantation (OLT) is associated with poor graft-and patientsurvival. Treatment with HBV-specific immunoglobulins (HBIG) in combination with nucleos(t)ide analogs is effective in preventing HBV reinfection of the graft and improving OLT outcome. However, the role of HBV-specific cellular immunity in viral containment in immune suppressed patients in general and in OLT recipients in particular is unclear. To test whether or not OLT recipients maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(58 reference statements)
0
5
1
Order By: Relevance
“…In contrast with reports in nontransplanted patients showing that antiviral‐induced control of the viral load results in transient restoration of HBV immunity,16 this increase has not been observed in patients with negative viremia after LT 20, 21. On the contrary, as reported by Luo et al,19 in patients with HBV recurrence after LT, the magnitude of T cell responses appears to be antigen‐driven and deleterious because T cell proliferative and secreting responses correlate to the viral load and alanine aminotransferase levels.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast with reports in nontransplanted patients showing that antiviral‐induced control of the viral load results in transient restoration of HBV immunity,16 this increase has not been observed in patients with negative viremia after LT 20, 21. On the contrary, as reported by Luo et al,19 in patients with HBV recurrence after LT, the magnitude of T cell responses appears to be antigen‐driven and deleterious because T cell proliferative and secreting responses correlate to the viral load and alanine aminotransferase levels.…”
contrasting
confidence: 57%
“…Interestingly, in the study by Luo et al,19 not all LT recipients with suppressed HBV replication showed an undetectable T cell response; a few of them had anti‐HBc reactivity similar to that of patients with resolved HBV infection. By studying a smaller number of LT patients with successful HBIG prophylaxis, Bihl et al21 recently provided evidence of a focused T cell response to HBc. By using a set of overlapping peptides in an interferon gamma enzyme‐linked immunosorbent spot assay (ELISPOT), they showed a narrow response to HBc peptides in LT patients but with a magnitude significantly higher than that in viremic patients and in patients with resolved infection and similar to that of chronically infected subjects with low viremia.…”
mentioning
confidence: 99%
“…HBsAg and HBV DNA were undetectable and anti-HBs very high the first three Table 1 Amino acid sequence and protein location of peptides targeted by the OLT recipient. A set of 208 overlapping peptides (OLP) was synthesized covering the entire HBV proteome including the nucleocapsid protein (24 peptides), envelope (53 OLP), X-protein (20 OLP) and polymerase protein (111 OLP) as described [13]. Peptides were adapted 18-mers overlapping by 10 amino acids and were based on the reported HBV genotype D reference strain ayw since HBV genotype D is predominant in Italy.…”
Section: Case Reportmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) were isolated as described [13], stimulated as outlined below and used in an interferon gamma (IFN c) based enzyme-linked immunospot (ELISpot) assay at 100,000 PBMC/well. ELISpot assays for all time points were performed at the same time and peptides were tested in 59 peptide matrix pools as described previously [15].…”
Section: Lymphocyte Isolation and Elispot Assaymentioning
confidence: 99%
See 1 more Smart Citation